On an exact description of the Schottky groups of symmetries - Dubatovskaya, M.V.; Rogosin, S.V. (Mathematical Modelling and Analysis, 2004)
Exact description of the Schottky groups of symmetries is given for certain special configurations of multiply connected circular domains. It is used in the representation of the solution of the Schwarz problem which is applied at the study of effective properties of composite materials.Apie Schottky simetrijos grupių tikslų apibrėžimąSantrauka. Darbe pateiktas Schottky simetrijos grupių apibrėžimas tam tikros specialios konfiguracijos daugiajungėms skritulinėms sritims. Jis yra panaudotas gaunant Švarco uždavinio, kuris pritaikomas nagrinėjant efektyvias kompozicijų savybes, sprendinio išraišką.First Published Online: 14 Oct 2010